Study on the Balanced Budget Multiplier - Samih Antoine Azar (Modern Perspectives in Economics, Business and Management Vol. 5, 2021)
This note has the purpose of deriving the balanced budget multiplier for disposable income. Under plausible conditions, it is demonstrated that this multiplier is equal to zero. This might explain the low level of empirical explanatory power of a balanced budget on aggregate output. The paper argues that a debt-financed government spending can be considered, under Ricardian equivalence, as a balanced budget fiscal policy. This also explains why the government spending multiplier is empirically found to be significantly less than one, and closer to zero than to one, while expectations are that it ought to be higher than 2. In addition, the note contends that consumption will be unresponsive to a balanced budget fiscal policy, and may actually fall. This should resonate badly in the assessment of the current stimulus packages embarked by Western nation governments to prop up aggregate demand given the fallouts of the pandemic. The risks are high that the stimulus programs may turn out to be less effective than expected by policy makers.